The preparation and catalytic performance of graphene-reinforced ion-exchange resins. Issue 4 (8th December 2014) - Li, Yanan; Yu, Fengping; He, Wenjun; Yang, Weimin
Abstract : The structural and thermal stability of graphene-based polymer nanocomposites were improved with chemical bonded interaction of graphene within the polymer networks. Abstract : Graphene-based polymer nanocomposites (GPNCs) were prepared by in situ suspension polymerization and the prepared polymers were chloromethylated with chloromethyl ethyl ether and then aminated with trimethylamine to obtain graphene-based nanocomposite ion-exchange resins (GPNC-IERs). Raman spectroscopy revealed the existence of a chemically bonded interaction between graphene and the polymer networks via the increased intensity and shift in the vibration bands of graphene in the nanocomposites. The reinforced thermal and structural properties of the nanocomposites were investigated with graphene contents from 0 to 1.0 wt%. The thermal stability was evaluated by thermogravimetric-differential thermal analysis (TG-DTA). It showed that the addition of graphene to the polymer matrix greatly increased the onset degradation temperature by 20 °C. The structural properties of the nanocomposites such as swelling capacity and total exchange capacity were improved with 0.4 wt% graphene, which confirmed that the good dispersion of graphene throughout the polymer matrix with strong interaction within the polymer networks played an important role in the properties enhancement effect. With the excellent anti-swelling property and thermal stability, the GPNC-IER catalysts presented a better performance in hydration of ethylene oxide (EO) to monoethylene glycol (MEG) including reaction activity, selectivity and stability in 500 h tests.